Development and validation of finite element model for the welded structure of transit bus. (17th October 2012) - Hu, Huiwen; Yang, Chung-Lin; Wang, Jieming
This paper aims at the development and validation of the Finite Element Model (FEM) of a welded structure for a transit bus. The integrated structure is generally fabricated by the assembly of several substructures, including the front-end, body-side, rear-end, roof, floor and chassis assemblies, through the welding and suspension linkages. A well-developed and validated FEM for such a complex and large structure is critical to the further structural analyses. Experimental Modal Analysis (EMA) is conducted on each substructure and then the integrated structure. The natural frequencies and the associated mode shapes obtained from EMA are used to validate those of from the FEA. Good correlation between EMA and FEA guarantees that the distributed stiffness and mass of the FEM are equivalent to the real vehicle structure. This validated model is then qualified for the further analyses such as structural stiffness, strength and impact crashes.